HUBUNGAN KEPERCAYAAN DIRI DAN KECEMASAN BERTANDING DENGAN MENTAL TOUGHNESS PEMAIN FUTSAL: STUDI ORELASIONAL PADA PEMAIN EKSTRAKURIKULER MA NW GONJONG - Erna Fitriatun; Sri Erny Muliyani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to examine the relationship between self-confidence and competition anxiety with mental toughness among futsal extracurricular players of MA NW Gonjong, Kopang District, Central Lombok Regency. This research employed a quantitative cross-sectional correlational design involving all 20 futsal players selected through saturated sampling. Data were collected using Likert-scale questionnaires measuring self-confidence, competition anxiety, and mental toughness, and were analyzed using descriptive statistics, assumption testing, and multiple regression with SPSS. The simultaneous test showed that self-confidence and competition anxiety were significantly associated with mental toughness (F = 4.457; p = 0.028). Based on the reported F value, the regression model explained approximately 34.4% of the variance in mental toughness, so the previously stated figures of 58.2% and 44.5% should not be interpreted as effective contributions unless recalculated from the complete SPSS output. Partially, self-confidence (t = 1.947; p = 0.068) and competition anxiety (t = 0.367; p = 0.718) did not show significant individual relationships with mental toughness. These findings indicate that futsal players’ mental toughness is better understood as a combined psychological condition, while causal interpretation should be avoided due to the correlational design and the small sample size. Keywords: self-confidence, competition anxiety, mental toughness, futsal players, correlational study Penelitian ini bertujuan untuk mengetahui hubungan antara kepercayaan diri dan kecemasan bertanding dengan mental toughness pemain ekstrakurikuler futsal MA NW Gonjong, Kecamatan Kopang, Kabupaten Lombok Tengah. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional potong lintang yang melibatkan seluruh pemain futsal sebanyak 20 orang melalui teknik sampling jenuh. Data dikumpulkan menggunakan angket skala Likert untuk mengukur kepercayaan diri, kecemasan bertanding, dan mental toughness, kemudian dianalisis dengan statistik deskriptif, uji asumsi, dan regresi berganda berbantuan SPSS. Hasil uji simultan menunjukkan bahwa kepercayaan diri dan kecemasan bertanding secara bersama-sama berhubungan signifikan dengan mental toughness (F = 4,457; p = 0,028). Berdasarkan nilai F yang dilaporkan, model regresi menjelaskan sekitar 34,4% variasi mental toughness, sehingga angka 58,2% dan 44,5% pada naskah awal tidak sebaiknya disebut sebagai sumbangan efektif sebelum dihitung ulang dari output SPSS yang lengkap. Secara parsial, kepercayaan diri (t = 1,947; p = 0,068) dan kecemasan bertanding (t = 0,367; p = 0,718) tidak menunjukkan hubungan individual yang signifikan dengan mental toughness. Temuan ini menunjukkan bahwa mental toughness pemain futsal lebih tepat dipahami sebagai kondisi psikologis yang terbentuk secara simultan, dengan tetap memperhatikan keterbatasan desain korelasional dan jumlah sampel yang kecil. Kata kunci: kepercayaan diri, kecemasan bertanding, mental toughness, pemain futsal, studi korelasional